Skeletal muscle modulation and functional recovery after colonic resection - Bhalla, Ashish (2016)
Introduction: Colorectal cancer surgery involves a period of recovery in hospital followed by convalescence at home. Enhanced recovery programs, in particular the use of laparoscopic surgery have reduced length of inpatient stay. Knowledge regarding the impact of surgery upon functional recovery is lacking. Loss of lean muscle mass and strength may compromise function. We conducted two studies (1) To assess skeletal muscle modulation and functional recovery after potentially curative colon cancer surgery, comparing traditional open surgery (OS) with laparoscopic (LS) techniques and (2) To review return to work (RTW) 1 year post colorectal cancer surgery.